IN FACT THE WAY OF SOLVING IS INCORRECT
(1-3/2)^2 = (2 - 3/2)^2
IS CORRECT BUT THIS DOES NOT MEAN THAT
1 = 2
(1-3/2) = -1/2
(2 - 3/2) = +1/2
ARE THEY EQUAL?
THERE MAY BE ANY REAL POSITIVE NUMBER X
X^2 = X*X (1)
(-X)^2 = (X*X)*(-1)^2 (2)
FROM (1) AND (2)
X = -X
IS THIS TRUE?
FOR YOUR CONVENIENCE,
THEIR IS ANOTHER PROOF OF 1 = 2
LET A = B
A^2 = A*B
A^2 - B^2 = A*B - B^2
(A+B)(A-B) = B(A-B)
A+B = B
A+A = A
2A = A
2 = 1
BUT DIFFERENCE OF 2 EQUAL NUMBERS IS ZERO.
A - B = 0
WE ALL KNOW THAT IT IS STUPIDNESS TO MULTIPLY SOMETHING BY 0 AND IS EVEN MORE THAN THAT TO DIVIDE BY IT.
THIS IS DONE IN THIS PROOF.
THERE ARE MANY WONDERS OF MATHEMATICS
IT CAN BE SEEN THAT 0! = 1
AND 1! = 1
DO IT MEAN 1= 0?
THINK IT CAREFULLY.
ONE CAN SEE THAT ALL MULTIPLES OF 9 ADD UP TO GIVE 9 ITSELF.
YOU CAN CHECK IT OUT.
9*1 = 9
9*2 = 18 1+8 = 9
9*3 = 27 2+7 = 9 ...
THIS IS TRUE.
2007-01-12 00:36:30
·
answer #1
·
answered by shrihanumanbhakta 2
·
1⤊
0⤋
That's a cute proof of the impossible. As another poster said, the trick is in cancelling the squares. The basic problem is that "a^2 = b^2" does not imply that "a=b"; we could also have "a=-b".
Would you agree that (-2)^2 = 2^2? But this doesn't imply that -2=2.
In your problem, 1-3/2 is -1/2, while 2-3/2 is 1/2. These numbers do indeed have the same square, but they have opposite signs.
2007-01-11 18:23:43
·
answer #2
·
answered by Doc B 6
·
2⤊
0⤋
You can do this by so many ways.one example is
16-36=25-45
=>16-36+(9/2)^2=25-45+(9/2)^2
=>(4)^2-2.4.9/2+(9/2)^2=(5)^2-2.5.9/2+(9/2)^2
=>(4-9/2)^2=(5-9/2)^2 and so on
But the real fact is that constants are constant and their value do not change under any circumstance.So neither can 2 be 3 or the value of 4 be 5.They would cease to be termed as constant if their value flactuates.
2007-01-11 20:22:49
·
answer #3
·
answered by alpha 7
·
1⤊
0⤋
No, guys... his trick is taking the square root. It is invalid here because the left side is -1/2 and the right side is +1/2. The numbers are not equal, but the squares of the numbers are.
2007-01-11 18:25:17
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
u cant just go replacing an non-variable equasion element like that in math...well REAL math.
sorry
numbers like 1, 2 and 1238 are called "constants" you can not change them around to fit your equasion. variables, however, like x, y, t and soforth you can swap around (like the name"variable" implies).
2007-01-11 18:11:15
·
answer #5
·
answered by Dashes 6
·
0⤊
1⤋
you lost me but the 'cancelling squares' move is the trick. you're dividing by zero there I think.
2007-01-11 18:13:16
·
answer #6
·
answered by hot.turkey 5
·
0⤊
2⤋
Actually you can replace integers with two integers. This is not the fault in these proofs.
2007-01-11 18:12:06
·
answer #7
·
answered by smawtadanyew 2
·
0⤊
2⤋
Can you say "ludicrous"?
2007-01-11 18:44:45
·
answer #8
·
answered by Helmut 7
·
0⤊
0⤋